(-3-8i)+(-5-7i)=0

Simple and best practice solution for (-3-8i)+(-5-7i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3-8i)+(-5-7i)=0 equation:


Simplifying
(-3 + -8i) + (-5 + -7i) = 0

Remove parenthesis around (-3 + -8i)
-3 + -8i + (-5 + -7i) = 0

Remove parenthesis around (-5 + -7i)
-3 + -8i + -5 + -7i = 0

Reorder the terms:
-3 + -5 + -8i + -7i = 0

Combine like terms: -3 + -5 = -8
-8 + -8i + -7i = 0

Combine like terms: -8i + -7i = -15i
-8 + -15i = 0

Solving
-8 + -15i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -15i = 0 + 8

Combine like terms: -8 + 8 = 0
0 + -15i = 0 + 8
-15i = 0 + 8

Combine like terms: 0 + 8 = 8
-15i = 8

Divide each side by '-15'.
i = -0.5333333333

Simplifying
i = -0.5333333333

See similar equations:

| 23.50+35= | | 12x+x-127=107 | | 3(-2x-2-3)-(-x+2)=-2(x+1) | | 48=(x+8)x | | Z+11=33 | | 35-3x=6x+22 | | -2x+4x-21=25 | | 27-17=5(x-9) | | 3n-2=106 | | -92+12x-2x=98 | | 6+2(x+5)=20 | | 8+2y=20 | | 26+4y-4=16y-14-3y | | 3G-2=106 | | 2(2x-4)=3(x+1) | | -62-x+8x=22 | | 5sinx+2=0 | | x+21+2x=-4-2x-10 | | 6x-50-2x=54 | | 5(f+9)=60 | | x-9/7+x+4/2=9/7 | | -111-4x+9x=39 | | x/5+1=6 | | 2a+1=21 | | -42-2x+7x=18 | | -(7y+2)-(-6y-8)=4 | | -4x-31+8x=65 | | 30+12(n-1)=102 | | 2n-1=37 | | -109+2x+5x=38 | | -2(4s-5)-10=-3(8s+1)-4 | | 4x^2-15x+29=6x+2 |

Equations solver categories